Detection of In Vivo Inflammasome Activation for Predicting Sepsis Mortality - Cui, Jing; Oehrl, Stephanie; Ahmad, Fareed; Brenner, Thorsten; Uhle, Florian; Nusshag, Christian; Rupp, Christoph; Funck, Felix; Meisel, Stefan; Weigand, Markus A.; Morath, Christian; Schäkel, Knut (Frontiers in Immunology, 2021)
Sepsis is a severe life-threatening syndrome caused by dysregulated host responses to infection. Biomarkers that allow for monitoring the patient’s immune status are needed. Recently, a flow cytometry-based detection of in vivo inflammasome activation by formation of cytoplasmic aggregates of ASC (apoptosis-associated speck-like protein containing a caspase recruitment domain) has been proposed. Here we report on the frequency of ASC-speck+ leukocytes correlating with the survival of sepsis. 25 patients with sepsis were sampled consecutively for 7 days. Blood, serum samples and patient data were collected according to the guidelines of the PredARRT-Sep-Trial. Flow cytometric analysis was performed on fresh whole blood samples to investigate the formation of ASC-specks in leukocyte subsets. Serum samples were analyzed for production of IL-1ß, IL-18 and additional inflammatory markers. ASC-speck formation was found to be increased in leukocytes from sepsis patients compared to healthy donor controls. The absolute number of ASC-speck+ neutrophils peaked on day 1. For monocytes, the highest percentage and maximum absolute number of ASC-speck+ cells were detected on day 6 and day 7. Inflammatory cytokines were elevated on day 1 and declined thereafter, with exception of IL-18. Survival analysis showed that patients with lower absolute numbers of ASC-speck+ monocytes (<1650 cells/ml) on day 6 had a lower probability to survive, with an hazard ratio (HR) of 10.178. Thus, the frequency of ASC-speck+ monocytes on day 6 after onset of sepsis may serve to identify patients at risk of death from sepsis.